2013
DOI: 10.1007/s00264-013-2240-7
|View full text |Cite
|
Sign up to set email alerts
|

Survival and functional outcome of the Birmingham Hip Resurfacing system in patients aged 65 and older at up to ten years of follow-up

Abstract: Purpose Limited evidence exists regarding the outcomes of hip resurfacing in elderly patients. The primary study aims were to determine the survival and functional outcome following Birmingham Hip Resurfacing (BHR) in patients ≥65 years at up to ten years of follow-up. Secondary aims were to explore factors affecting survival and functional outcome. Methods Between 1997 and 2012, data were prospectively collected on 180 BHR (162 patients; mean age 69.2 years; 62 % male) implanted by one designing surgeon. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…On occasions experienced surgeons may also wish to consider older patients for HR provided they are active and meet all other proposed indications. This is because chronological age was not originally cited as an absolute contraindication to HR [41], with good medium-term to long-term outcomes reported by experienced surgeons in patients aged over 60 years [27,57]. In addition, although there have been some case reports of adverse outcomes in patients receiving staged bilateral MoM HRs [58,59], medium to long-term outcome studies for the BHR suggest bilateral implantation in suitable candidates is safe [26,27,30,60].…”
Section: Future Role Of Hip Resurfacingmentioning
confidence: 99%
“…On occasions experienced surgeons may also wish to consider older patients for HR provided they are active and meet all other proposed indications. This is because chronological age was not originally cited as an absolute contraindication to HR [41], with good medium-term to long-term outcomes reported by experienced surgeons in patients aged over 60 years [27,57]. In addition, although there have been some case reports of adverse outcomes in patients receiving staged bilateral MoM HRs [58,59], medium to long-term outcome studies for the BHR suggest bilateral implantation in suitable candidates is safe [26,27,30,60].…”
Section: Future Role Of Hip Resurfacingmentioning
confidence: 99%
“…At the previous consensus meeting in 2012 there was no agreement with regard to the necessity of performing a DEXA scan in all females older than 55 years (39.4% were advocates, 42.3% found that unnecessary but would assess the bone quality on x-rays and in relation with the patient's general health and activity level and 18.3% would perform DEXA scans in cases of doubt). However, it was advocated in 2012 and in 2014 to primarily consider the physiological age of the patient based on activity level and bone quality at the hip which is confirmed by studies showing no significant difference between THA and HRA especially in older men (17-18-19). With our ageing population remaining more active and healthy for a longer period of time, the physiological age is the most stringent argument in the decision whether or not to perform a hip resurfacing.…”
Section: Results Of the Consensus Votings And Discussionmentioning
confidence: 99%
“…Qualitative studies show that older adults have high expectations concerning physical health and level of activity. Recent studies have demonstrated low rates of revision and improved patient-reported outcome measures (PROMs) in older patients who underwent HRA [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%